2007
DOI: 10.1111/j.2007.0030-1299.15382.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing intraspecific diversity increases predictability in population survival in the face of perturbations

Abstract: It has been proposed that biodiversity can be important for ecosystem functioning and act as an insurance against perturbations and environmental fluctuations. To date, theoretical work supports this idea but direct experimental evidence is still to some extent ambiguous and debated. The main reason for this debate Á and the lack of strong empirical support Á is due to unavoidable experimentally and statistically inherent variance reduction effects. Here we present the results of an experimental study that cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…Five experimental studies that compared dynamics of populations with different degree of genetic variation under laboratory conditions concur that higher diversity reduces fluctuations in population size (Imura et al 2003, Gamfeldt and Källström 2007, Agashe 2009, Agashe and Bolnick 2012, Ramsayer et al 2013 (Table 1). In a host-parasitoid systems with Callosobruchus chinensis weevils, Imura et al (2003) found stabilized (i.e.…”
Section: Population Stabilitymentioning
confidence: 94%
See 2 more Smart Citations
“…Five experimental studies that compared dynamics of populations with different degree of genetic variation under laboratory conditions concur that higher diversity reduces fluctuations in population size (Imura et al 2003, Gamfeldt and Källström 2007, Agashe 2009, Agashe and Bolnick 2012, Ramsayer et al 2013 (Table 1). In a host-parasitoid systems with Callosobruchus chinensis weevils, Imura et al (2003) found stabilized (i.e.…”
Section: Population Stabilitymentioning
confidence: 94%
“…less fluctuating) population dynamics in mixed host populations of hybrid individuals, compared with genetically less variable pure host strains. Gamfeldt and Källström (2007) compared survival of individuals in populations of Gammarus duebeni amphipods with different degree of genetic variation in treatments with or without desiccation, and found that mean number of survivors did not differ according to degree of variation, but in the desiccation treatment, variance in number of survivors decreased with increased genetic variation. Agashe (2009) found that stability, represented by the inverse of the coefficient of variation (CV) of population size, was higher in genetically more variable populations of Tribolium castaneum flour beetles, independent of whether the selective habitat (food resources) was ancestral (wheat) or novel (corn).…”
Section: Population Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies have begun to demonstrate that intraspecific variation does indeed affect ecological processes. Experimental populations with greater intraspecific genetic and phenotypic diversity often have greater resistance to disturbance (Hughes and Stachowicz 2004;Gamfeldt and Källström 2007) greater mean individual fitness (Johnson et al 2006), and support more diverse ecological communities (Hughes and Stachowicz 2004;Johnson et al 2006, Crutsinger et al 2008. Similarly, when competition within communities increases, individuals with more extreme phenotypes have higher relative fitnesses than individuals with more common phenotypes (Bolnick 2004).…”
Section: Introductionmentioning
confidence: 97%
“…A high N e indicates a higher number of contributing broodstock to a population, and can be a valuable gauge of how e⁄ciently an aquaculture operation is capturing or maintaining genetic diversity. This is important, as su⁄cient levels of genetic diversity within aquaculture populations can provide stability in the face of environmental disturbances (Gamfeldt & Kallstrom 2007) and will maximize the long-term response to selective breeding through genetic improvement programmes (Davis & Hetzel 2000). Maintaining a high N e will also reduce the risk of encountering problems associated with inbreeding, which have been well documented in aquaculture species (e.g.…”
Section: Introductionmentioning
confidence: 99%